Normal values for hip muscle strength and range of motion in elite, sub-elite and amateur male field hockey players - Beddows, T. P.A.; van Klij, P.; Agricola, R.; Tak, I. J. R.; Piscaer, T.; Verhaar, J. A. N.; Weir, A. (Physical Therapy in Sport, 2020)
Study presents normal values for hip strength and range of motion in field hockey. No influence of leg dominance, playing position/level and non-time-loss groin pain. Normal values can be used to identify players at risk for hip/groin injuries.